DARI DEPOK LAMA KE DEPOK BARU: Berjuang Menjadi Kota, 1970an – 1990an - Tri Wahyuning Mudaryanti (SASDAYA: Gadjah Mada Journal of Humanities, 2016)
This research deals with the process of spatial development in the city of Depok, West Java and its relation to the government’s policy during 1970s – 1990s. Administratively, it has become a city which is separated from the capital Jakarta since 1999, but Depok is struggling to establish its own identity. In the beginning, Depok was designed to solve the urban problems of Jakarta. In the later period, Depok experienced a slow progress for new urban area. This is due to the government’s policy that continues to treat Depok as a supporting city of Jakarta. On the other hand, the presence of Universitas Indonesia in Depok fails to support the creation of an autonomous city of Depok.